IAFR Guidelines for best practice: Principles for radiographers and imaging practitioners providing forensic imaging services. (September 2020) - Doyle, Edel; Hunter, Paul; Viner, Mark D.; Kroll, Jeroen J.K.; Pedersen, Christina Caroe; Gerrard, Chandra Y.
Highlights: IAFR guidelines for radiographers, managers or planners Provision of forensic imaging services Summary: Radiography for forensic purposes is a complex area of practice and the International Association of Forensic Radiographers (IAFR) is pleased to provide this guidance and advice document for Radiographers and Radiological Technologists involved in providing forensic imaging services. These guidelines were originally published as a collaboration between the IAFR and the College of Radiographers in the United Kingdom (UK), in 1998 [1] . As membership of the IAFR continues to grow internationally, these guidelines have now been updated to be more applicable outside the UK justice system [2] . The aim is that the principles outlined in these international 'best-practice' guidelines will be adapted by national professional bodies and relevant health and justice departments to suit local medico-legal systems within each country, and that departmental managers and employers should also find this document invaluable [3] . It is recognised that the level of best practice that can be achieved is dependent on local facilities and resources, as well as the expertise of the radiographer(s).